Penguatan Kelembagaan dalam Mewujudkan Kabupaten Banyuwangi Sehat - Jauhariyah, Nur Anim; Syafa'at, Ahmad Munib; Mahmudah (Universitas KH. Mukhtar Syafaat (UIMSYA), 2024)
Banyuwangi Regency is located at the tip of East Java Island which has beautiful tourism and culture that can boost the community's economy. The purpose of this community service is to analyze the potential and provide education to the community regarding the importance of implementing a clean, healthy, safe, and comfortable life both in the family environment, work environment, and society through institutional strengthening. The location of the community service was carried out in Siliragung District which consists of five villages and monitoring was carried out once every six months every year. The results of the community service show that the institutions in the Healthy District Communication Forum in Siliragung District and the Healthy Village Working Group in Seneporejo, Siliragung, Kesilir, Buluagung, and Barurejo Villages have carried out activities that are in synergy with the Banyuwangi Regency government program, so that they can support in eradicating the problems in the area. However, there are weaknesses in the management of the Parangsemar tourist destination and sustainable waste management that need to be continuously accompanied and fully supported by each sector.